EXOPRODIGI - Digital tools for eco-efficient maritime industry - Ajanko Julia (Turun yliopisto, 2022)
The Baltic Sea as a transport route has a long history. Even today the sea is a busy place in terms of shipping. At any given moment, there are around 2000 ships in the Baltic Sea, utilizing around 100 internationally important ports around the region to load and discharge their cargo and passengers. In addition to shipping and ports, the importance of the shipbuilding industry at the Baltic Sea is well recognized. At the same time, as any other transport mode still mainly relying on fossil fuels, shipping causes negative impacts on the environment.
The Baltic Sea is particularly sensitive to the environmental pressure resulting from ceaseless human activities. As one of the world’s largest reservoirs of brackish water, the Baltic Sea is ecologically unique. More than 85 million people populate the coastal regions around the Baltic Sea; thus, the sea and its catchment area are imposed on a magnitude of human activities and pressure.
New digital maritime solutions can open up new business opportunities for the Baltic Sea region, but what more, digitalization can contribute to more environmentally friendly human actions and to diminishing pressure on the sensitive Baltic Sea marine environment.
The aim of the EXOPRODIGI project (2021) was to improve the eco-efficiency of the maritime industry with the help of digital tools and solutions. The project concentrated on three key areas of the maritime industry: 1) digital performance monitoring, 2) cargo stowage optimization, and 3) optimising shipyard processes.
This synthesis sheds light on the digital tools and solutions developed during the EXOPRODIGI project from a practical point of view. How do the new solutions function? Which benefits do they bring? How can they enhance the eco-efficiency and sustainability of the maritime industry? The work done in EXOPRODIGI builds on the findings of a previous three-year-long ECOPRODIGI project (2017-2020).